Analysis of the optimal trajectory in weightlifting in style "snatch" - Zamora, D.; Rodas, P.; Pauzhi, W.; Zumba, P.; Duchitanga, J.; Urgiles, F. (2015 CHILEAN Conference on Electrical, Electronics Engineering, Information and Communication Technologies (CHILECON), 2015)
The paper presents a comparative analysis of the data obtained from the vertical trajectory of the bar during weightlifting in the snatch mode, these amateur athletes will be compared to an elite athlete in weightlifting, in order to obtain velocities and accelerations for the evaluation of the technique used in each phase. The Lagrange interpolation method was used to obtain a mathematical representation a function of time describing the trajectory of the bar during the uprising in the snatch mode, to thereby obtain the speed and acceleration during the lifting of the bar at every phase.